Drug-loaded pseudo-block copolymer micelles with a multi-armed star polymer as the micellar exterior. Issue 29 (6th July 2015) - Xie, Chen; Zhang, Peng; Zhang, Zhengkui; Yang, Chenchen; Zhang, Jialiang; Wu, Wei; Jiang, Xiqun
Abstract : A novel kind of PVP–PCL pseudo block polymer based on multi-armed CD-PVP and adamantane-terminated PCL was synthesized. The effect of the PVP chain number on the properties of PVP–PCL micelles were studied. Abstract : Supramolecular constructed pseudo block copolymer micelles based on β-cyclodextrin terminated 4 and 7 armed star poly( N -vinylpyrrolidone) and adamantane terminated linear poly(ε-caprolactone) were prepared. The size, morphology, stability and protein adsorption were experimentally examined. The micelles with 7 armed PVP chains as the micellar exterior showed the lowest amount of protein adsorption and the best stability in media. When cabazitaxel, a new taxane, was loaded into the micelles, 14.4% drug loading content and 85% encapsulation efficacy were achieved. In vitro cytotoxicity studies demonstrated that the cabazitaxel-loaded micelles show significant cytotoxicity against drug-resistant A2780/T cell lines. Biodistribution studies showed that the micelles can almost double the content of cargo in tumor sites compared with the free cargo. In vivo antitumor activity examinations indicated that cabazitaxel-loaded micelles show superior antitumor activity over free paclitaxel and free cabazitaxel.